2002
DOI: 10.1016/s0736-0266(02)00047-5
|View full text |Cite
|
Sign up to set email alerts
|

The adaptation of soleus and edl in a rat model of distraction osteogenesis: IGF‐1 and fibrosis

Abstract: The distraction rate of 0.5 mm/day produces good osteogenesis in small rodents; however, the effects of this distraction rate on muscle are not well documented. We evaluated the soleus and the extensor digitorum longus (EDL) after two weeks of lengthening distraction osteogenesis (DO) at 0.5 mm/day in skeletally mature rats. We found a modest but significant local increase of insulin like growth factor-1 (IGF-1) in the EDL, however, muscle growth indicated by developmental forms of myosin heavy chain (MHC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
12
1
1
Order By: Relevance
“…Although in this study, no adequate labeling was done to rule out definitely an ongoing process of sarcomere neogenesis, the amount of stretching of the sarcomeres was enough to account mathematically for the recorded increase in FL at this time point, suggesting that the number of sarcomeres in series probably did not significantly change after lengthening. This appears to be in contrast to previous reports, which indicated that distraction osteogenesis stimulated muscle growth (Day et al, 1997a;De Deyne, 2002;De Deyne et al, 2002) and induced adding new sarcomeres in se- Fig. 4.…”
Section: Discussioncontrasting
confidence: 96%
“…Although in this study, no adequate labeling was done to rule out definitely an ongoing process of sarcomere neogenesis, the amount of stretching of the sarcomeres was enough to account mathematically for the recorded increase in FL at this time point, suggesting that the number of sarcomeres in series probably did not significantly change after lengthening. This appears to be in contrast to previous reports, which indicated that distraction osteogenesis stimulated muscle growth (Day et al, 1997a;De Deyne, 2002;De Deyne et al, 2002) and induced adding new sarcomeres in se- Fig. 4.…”
Section: Discussioncontrasting
confidence: 96%
“…Several studies have shown that growth factors play a variety of roles during muscle regeneration (Gospodarowicz et al, 1976; Inselburg and Applebaum, 1978; Linkhart et al, 1981; Florini et al, 1986; Olson et al, 1986; Allen and Boxhorn, 1989; Jennische, 1989; Jin et al, 1990; Yablonka-Reuveni et al, 1990; Anderson et al, 1991; Grounds, 1991; Harrington et al, 1992; Doumit et al, 1993; McFarland et al, 1993; Barnard et al, 1994; Coleman et al, 1995; Johnson and Allen, 1995; Jones and Clemmons, 1995; Lefaucheur and Sebille, 1995; Zdanowicz et al, 1995; Chambers and McDermott, 1996; Engert et al, 1996; Florini et al, 1996; Papadakis et al, 1996; Quinn and Haugk, 1996; Floss et al, 1997; Kurek et al, 1997; Lamberts et al, 1997; Barton-Davis et al, 1998; Damon et al, 1998; Springer et al, 1998; Tatsumi et al, 1998; Keller et al, 1999; Gowdak et al, 2000; Sheehan et al, 2000; De Deyne et al, 2002; Musaro et al, 2004; Wieteska-Skrzeczynska et al, 2011a,b). Using a mouse model, Menetrey et al (2000) found that direct injections of insulin-like growth factor-1 (IGF-1), basic fibroblastic growth factor (bFGF), and, to a lesser extent, nerve growth factor (NGF), led to enhanced muscle healing in lacerated, contused, and strain-injured muscle at 2, 5, and 7 days after injury.…”
Section: Muscle Regenerationmentioning
confidence: 99%
“…Many reports have shown that growth factors play a variety of roles during muscle regeneration [Gospodarowicz et al, 1976;Linkhart et al, 1981;Florini et al, 1986;Olson et al, 1986;Allen and Boxhorn, 1989;Jennische, 1989;Jin et al, 1990;Yablonka-Reuveni et al, 1990;Anderson et al, 1991;Grounds, 1991;Harrington et al, 1992;Doumit et al, 1993;McFarland et al, 1993;Barnard et al, 1994;Coleman et al, 1995;Johnson and Allen, 1995;Jones and Clemmons, 1995;Lefaucheur and Sebille, 1995;Zdanowicz et al, 1995;Chambers and McDermott, 1996;Engert et al, 1996;Florini et al, 1996;Papadakis et al, 1996;Quinn and Haugk, 1996;Floss et al, 1997;Kurek et al, 1997;Lamberts et al, 1997;Barton-Davis et al, 1998;Damon et al, 1998;Springer et al, 1998;Tatsumi et al, 1998;Keller et al, 1999;Gowdak et al, 2000;Sheehan et al, 2000;De Deyne et al, 2002;Musaro et al, 2004]. Direct injections of insulin-like growth factor (IGF)-1, basic fibroblast growth factor (bFGF), and, to a lesser extent, nerve growth factor (NGF), were found to enhance skeletal muscle healing in several mouse muscle injury models …”
Section: Various Approaches Can Be Used To Improve Muscle Regenerationmentioning
confidence: 99%